Status of newborn screening and follow up investigations for Mucopolysaccharidoses I and II in Taiwan - Chih-Kuang Chuang; Hsiang-Yu Lin; Tuan-Jen Wang; You-Hsin Huang; Min-Ju Chan; Hsuan-Chieh Liao; Yun-Ting Lo; Li-Yun Wang; Ru-Yi Tu; Yi-Ya Fang; Tzu-Lin Chen; Hui-Chen Ho; et al. (Orphanet Journal of Rare Diseases, 2018)
Abstract Background Mucopolysaccharidoses (MPS) are lysosomal storage diseases in which mutations of genes encoding for lysosomal enzymes cause defects in the degradation of glycosaminoglycans (GAGs). The accumulation of GAGs in lysosomes results in cellular dysfunction and clinical abnormalities. The early initiation of enzyme replacement therapy (ERT) can slow or prevent the development of severe clinical manifestations. MPS I and II newborn screening has been available in Taiwan since August 2015. Infants who failed the recheck at recall were referred to MacKay Memorial Hospital for a detailed confirmatory diagnosis. Methods From August 2015 to November 2017, 294,196 and 153,032 infants were screened using tandem mass spectrometry for MPS I and MPS II, respectively. Of these infants, 84 suspected cases (eight for MPS I; 76 for MPS II) were referred for confirmation. Urinary first-line biochemistry examinations were performed first, including urinary GAG quantification, two-dimensional electrophoresis, and tandem mass spectrometry assay for predominant disaccharides derived from GAGs. If the results were positive, a confirmative diagnosis was made according to the results of leukocyte enzymatic assay and molecular DNA analysis. Leukocyte pellets were isolated from EDTA blood and used for fluorescent α-iduronidase (IDUA) or iduronate-2-sulfatase (IDS) enzymatic assay. DNA sequencing analysis was also performed. Results Normal IDS and IDUA enzyme activities were found in most of the referred cases except for four who were strongly suspected of having MPS I and three who were strongly suspected of having MPS II. Of these infants, three with novel mutations of the IDS gene (c.817C > T, c.1025A > G, and c.311A > T) and four with two missense mutations of the IDUA gene (C.300-3C > G, c.1874A > C; c.1037 T > G, c.1091C > T) showed significant deficiencies in IDS and IDUA enzyme activities (< 5% of mean normal activity), respectively. Urinary dermatan sulfate and heparan sulfate quantitative analyses by tandem mass spectrometry also demonstrated significant elevations. The prevalence rates of MPS I and MPS II in Taiwan were 1.35 and 1.96 per 100,000 live births, respectively. Conclusions The early initiation of ERT for MPS can result in better clinical outcomes. An early confirmatory diagnosis increases the probability of receiving appropriate medical care such as ERT quickly enough to avoid irreversible manifestations. All high risk infants identified in this study so far remain asymptomatic and are presumed to be affected with the attenuated disease variants.